Investigation of Artocarpus Heteropyllus peel extract as non-toxic corrosion inhibitor for pure copper protection in nitric acid. (December 2022) - Kusumaningrum, Ira; Soenoko, Rudy; Siswanto, Eko; Gapsari, Femiana
Abstract: Artocarpus Heteropyllus Peel as non-toxic fruit waste contained some antioxidants. Peel extract of Artocarpus Heteropyllus could used as inhibitor to reduced corrosion rate. In this study, artocarpus heteropyllus peel extract was used as inhibitor corrosion to protect pure copper in 1 M HNO3 . The inhibitor concentration was varied of 0–800 ppm. The measurement of corrosion rate was conducted by applying potentiodynamic polarization methods. The inhibitor performance, isotherm adsorption the thermodynamic parameter and kinetic activation energy were analyzed. Artocarpus heteropyllus peel extract was mixed inhibitor type and tended to anodic inhibitor type. The highest inhibitor efficiency was 98%. It occurred at its concentration of 800 ppm and temperature of 25 °C. Isothermic adsorption pattern followed the Frumkin adsorption isotherm equation. Inhibitor molecules were adsorbed on the pure copper surface physically. Graphical abstract: Image 1 Highlights: Artocarpus Heteropyllus peel extract is efficient inhibitor for the pure copper corrosion in nitric acid. The type inhibitor is mixed inhibitor and tends to anodic inhibitor. Isothermic adsorption pattern followed the Frumkin adsorption isotherm equation. Inhibitor molecules adsorbs on the pure copper surface physically. The result of experimental accords with the theoretical.